2020
DOI: 10.1158/1055-9965.epi-19-1446
|View full text |Cite
|
Sign up to set email alerts
|

Objectively-Measured Light-Intensity Physical Activity and Risk of Cancer Mortality: A Meta-analysis of Prospective Cohort Studies

Abstract: Background: The impact of light-intensity physical activity (LPA) in preventing cancer mortality has been questioned. To address this concern, the present meta-analysis aimed to quantify the association between objectively-measured LPA and risk of cancer mortality. Methods: We conducted a systematic literature search in PubMed and Scopus to January 2020. Prospective cohort studies reporting the association between objectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…For this population, LPA may represent a desirable alternative. Together with the evidence that LPA could help to reduce the risk of all-cause and cancer death in older adults [26,31] and given that increased LPA is associated with improved cognitive functioning [32] and a better profile of cardiometabolic control [33], our findings suggest that LPA should be routinely recommended for older adults, and advice on how to promote LPA (e.g., using pedometers to increase daily physical activity [34]) should be integrated into clinical practice.…”
Section: Interpretations and Implicationssupporting
confidence: 52%
“…For this population, LPA may represent a desirable alternative. Together with the evidence that LPA could help to reduce the risk of all-cause and cancer death in older adults [26,31] and given that increased LPA is associated with improved cognitive functioning [32] and a better profile of cardiometabolic control [33], our findings suggest that LPA should be routinely recommended for older adults, and advice on how to promote LPA (e.g., using pedometers to increase daily physical activity [34]) should be integrated into clinical practice.…”
Section: Interpretations and Implicationssupporting
confidence: 52%
“…However, sensitivity analysis revealed similar associations with total cancer when subdividing cohorts by diabetes ascertainment (self-reported vs. documented). We also cannot exclude the possibility of residual confounding from unmeasured confounding factors, including diet, blood lipid concentrations and blood pressure, and by incomplete adjustment for physical activity, because both moderate-to-vigorous and light-intensity physical activity have also been shown to reduce cancer mortality (44) and the risk of breast ( 45) and total cancer (46).…”
Section: Discussionmentioning
confidence: 99%
“…However, even in the non-epidemic period, in many countries, 80% or more adolescents do not meet the current World Health Organization physical activity recommendations [ 9 ]. A survey of 187 countries showed that physical activity during COVID-19 decreased compared to normal [ 10 ], which may have implications on health, such as increased risk of cancer, heart disease, stroke, and diabetes [ 11 , 12 , 13 , 14 ]. Compared to these potential risks that are easily ignored, the decline of physical fitness caused by physical inactivity can be evaluated and observed more directly.…”
Section: Introductionmentioning
confidence: 99%